Anaesthetic management of a dog with severe pulmonary stenosis and R2A right coronary artery anomaly undergoing placement of a hybrid transventricular pulmonary stent. Issue 2 (25th February 2022) - Cambruzzi, Martina; Borgeat, Kieran; MacFarlane, Paul
Abstract: A 7‐month‐old, 12.2 kg, male, neutered, English bulldog with severe pulmonary stenosis and R2A right coronary artery anomaly was anaesthetised for placement of hybrid right ventricle to pulmonary artery stent. An alfentanil bolus (10 μg/kg intravenously) was used as premedication. Anaesthesia was induced with midazolam (0.2 mg/kg) and etomidate (1 mg/kg) intravenously, and maintained with sevoflurane in 100% oxygen. Perioperative analgesia was achieved combining locoregional techniques with intravenous analgesics. The main intraoperative complications were hypotension, bradycardia, ventricular premature complexes, ST‐segment depression and transient hypoxaemia. Lidocaine constant‐rate infusion (50 μg/kg/min) and magnesium sulphate constant‐rate infusion (5 mg/kg/h) were used to prevent arrhythmias during the cardiac manipulations and stent placement. Hypotension was treated with dobutamine and noradrenaline constant‐rate infusion. The use of different drugs and anaesthetic techniques (balanced anaesthesia) provided antinociception, muscle relaxation and appeared to be effective in preventing major cardiovascular complications.